An endophytic strain of genus Paenibacillus isolated from the fruits of Noni (Morinda citrifolia L.) has antagonistic activity against a Noni's pathogenic strain of genus Aspergillus. (December 2018) - Liu, Yang; Bai, Feirong; Li, Ting; Yan, Hai
Abstract: Endophytes are microbes capable of colonizing the tissues of healthy plants and subsequently establishing a harmonious relationship with their hosts. In this research, the endophytic strain Paenibacillus sp. NEB was isolated from fruits of healthy Noni ( Morinda citrifolia L.). Strain NEB was identified as Paenibacillus polymyxa using MALDI-TOF Mass Spectrometry. Pathogenic fungal strain NP-1 was isolated from Noni fruits infected by smut, and was identified as Aspergillus aculeatus by polyphasic taxonomy basing on morphological identification, and ITS-5.8S rDNA and β-tubulin gene phylogenetic analyses. Through the antagonistic test against the pathogenic strain Aspergillus aculeatus NP-1, the results showed that strain NEB had a good antagonistic activity against smut pathogen of Noni. By sequencing with Illumina HiSeq 2000, the draft genome of Paenibacillus sp. NEB was acquired, and 3 CDSs for glucanases were annotated and potentially correlated to the antagonistic activity of this strain. Using realtime-PCR method with specific primers to amplify the biocontrol gene, β-1, 3-1, 4- glucanase gene ( gluB ), it was found in Paenibacillus polymyxa NEB. This study would provide a theoretical and microbial basis for the rationally developing and using Noni beneficial microbial inoculants against its pathogenic strain in the future. Highlights: The endophytic strain Paenibacillus sp. NEB was isolated from fruits of healthy Noni ( Morinda citrifolia L.). Strain NEB was identified as Paenibacillus polymyxa . Pathogenic fungal strain NP-1 was isolated from Noni fruits infected by smut, and was identified as Aspergillus aculeatus by polyphasic taxonomy. Through the antagonistic test against the pathogenic strain NP-1, the results showed that strain NEB had a good antagonistic activity against smut pathogen of Noni. And the biocontrol gene gluB was amplified in Paenibacillus polymyxa NEB.